The Association of High-Frequency Nut Intake With a Low Risk of Psychological Problems in Female Methamphetamine Users - Song, Zihong; Dong, Fang; Liu, Yizhi; Liu, Guanhua; Li, Baohua; Pang, Xiuyu; An, Kang; Li, Dong; Chen, Shanshan; Xing, Weijia; Xu, Xizhu (Frontiers in Psychiatry, 2022)
Background: Recent years has witnessed the gradual increase in the number of female methamphetamine users. Meanwhile, female methamphetamine users are more likely to have psychological problems than male methamphetamine users. The association of diet and psychological problems have been found among non-methamphetamine user population. The present study aims to investigate the relationship between dietary intake frequency and psychological problems in female methamphetamine users. Methods: A total of 109 female methamphetamine users, collected from a Compulsory Isolated Drug Rehabilitation Centre in northern China, participated in the study. All participants completed the Symptom Checklist 90 (SCL-90) questionnaires to assess psychological status. The relation of dietary intake frequency with SCL-90 score was tested in partial correlation analysis. Multivariable regression models were used to calculate odds ratios (ORs) to evaluate the association of dietary intake frequency with psychological problems. Results: In current female methamphetamine population, 33 participants were diagnosed with psychological problems using SCL-90. In terms of dietary intake frequency, the frequency of nut intake in the psychiatric symptom group was significantly lower than that in the asymptomatic group. However, there was no difference in the frequency of other food intake between the two groups. The frequency of nut intake was negatively correlated with the scores of total and 7 different symptom clusters of psychopathologies of SCL-90. Logistic regression analysis indicated that the increased frequency of nut intake was associated with lower risk of psychological problems. Conclusions: In the female methamphetamine population, increasing the frequency of nut intake may reduce the risk of psychological problems of female methamphetamine users.